2007
DOI: 10.1080/01421590701754128
|View full text |Cite
|
Sign up to set email alerts
|

Teaching professionalism: a South African perspective

Abstract: Background: Incorporating the teaching and assessment of professionalism in an undergraduate medical curriculum is a challenging process. There are two components that require attention: the cognitive and the experiential. This article outlines how the School of Medicine at the University of Pretoria (UP), South Africa is addressing the teaching and assessment of professionalism. Aims: To embed teaching and assessment of professionalism in a revised six-year undergraduate medical curriculum. Method: This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…These are in line with the approaches used by some institutions to integrate professionalism into the formal curriculum[24,27]. Other institutions use longitudinal individual assignments which are assessed, and for which students receive feedback[29,31]. …”
Section: Resultssupporting
confidence: 58%
“…These are in line with the approaches used by some institutions to integrate professionalism into the formal curriculum[24,27]. Other institutions use longitudinal individual assignments which are assessed, and for which students receive feedback[29,31]. …”
Section: Resultssupporting
confidence: 58%
“…There is growing consensus among medical educators that, to promote the professional development of medical students, schools of medicine should provide explicit learning experiences in professionalism (Swick et al 1999, Du Preez et al 2007). Concurrently, it has been demonstrated that clinical simulations could lead to effective learning (Issenberg et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing consensus among medical educators that, to promote the professional development of medical students, schools of medicine should provide explicit learning experiences in professionalism (Swick et al. 1999, Du Preez et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Often this posed an ethical conundrum for students seeking to uphold high standards of humanism and professionalism. Such observations of lapses in professionalism and encroachment on patient rights have previously been documented in Africa [ 13 , 14 ] as well as in Western settings [ 15 18 ]. Role-modeling and structured reflection have been identified as means of engendering professional values of empathy, altruism, and shared-decision making in a variety of contexts [ 19 21 ].…”
Section: Discussionmentioning
confidence: 72%